Effects of Biodiesel Towards CI Engine Performance and Emission: A Brief Review - Azlan, K.A.; Tamaldin, N.; Abdollah, M.F.B. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Biodiesel is a biofuel that has great potential to become an alternative fuel as it can be directly used in the Compression Ignition (CI) engine with very little or without any modification needed. From this review, it is identified that the quality of the biodiesel produced and the final performance of the engine is mainly depending on biodiesel feedstock, biodiesel production and engine technology. Different feedstock has a different composition, hence will produce biodiesel with different fuel properties that contribute to engine performance and emission. Nevertheless, proper production process and advanced engine technology can overcome the biodiesel drawback.